Studies on HPV Infection and Persistence in a University Undergraduate Population - Bibby, Elisa (My University, 1999)
Cervical cancer is preceded by a spectrum of abnormalities in the cervical epithelium. Research supports an etiological role for certain types of human papillomaviruses (HPVs) in cervical pathology. More than 70 HPV genotypes have been characterized based on complete genome sequences and of these, about half infect the genital tract. Genital HPVs are further classified as either "high risk" or "low risk" types based on their association with cervical cancer. The demonstration that there is a relationship between HPV infection and cervical cancer has been dependent on a number of viral nucleic acid-based detection systems such as Southern blot and polymerase chain reaction. However, the lack of methods which discriminate between a specific HPV type and a large number of related HPV genotypes has made studies of disease association difficult. In the first part of this study, a recently developed Amplicor HPV Genotyping Kit was evaluated with respect to its ability to define HPV infection status. The L1 region was directly sequenced from the PCR product in 16 clinical samples to determine which genotype(s) was/were present. Sequencing data from one sample suggested a mixed infection and therefore the PCR product was cloned and sequenced to see if more than one genotype was present. Fifteen out of the sixteen samples sequenced were HPV genotypes which are not represented on the Amplicor Genotyping Kit test strips. The samples are rare HPV types (HPV 61, 62, CP6108 and CP8304). The second part of this study examined the issue of persistence and in particular, I have considered the issue of an appropriate definition of persistence. A number of patients who had evidence of HPV 16 or HPV 18, 6 and 66 were investigated using samples obtained on at least two occasions. Molecular variants of either the LCR gene for HPV 16 or the L1 gene for the other HPV types were studied. No differences in LCR or L1 gene sequence in sequential same patient samples were observed. Two HPV 16 LCR alleles were seen for six patients of which 8/10 showed one nucleotide change at base 7518 and 2/10 were identical to the prototype. Based on a compilation of published studies on HPV 16 variants and subtypes for the long control region, the number of HPV 16 LCR alleles, worldwide, was determined. One HPV 66 and two HPV 18 and HPV 6 L1 alleles were observed. When examining persistence, one must consider the frequency of specific variants (alleles) in the study population. A common variant detected over time could either be a persistent infection or a reinfection with the same viral variant.
HPV Infection and Persistence
Keywords: HPV; population; infect; persist